Chromaliving. - Jocelyn, Tim; Fabo, Andy (Toronto : Chromazone/Chromatique, 1983)
Abrams, John ; Allikas, Barry ; Anderson, David ; Anderson, Jim ; Andrews, Stephen ; Angliss, Kim ; Astman, Barbara ; Baird, Rebecca ; Balicki, Roman ; Banks, Richard ; Parker, Phillip ; Beninger, Aileen ; Bourque, Anna ; Bowers, Robert ; Bowley, Janis ; Brenot, Blair ; Brown, William ; Broze, Modris ; Buchan, David ; Burnett, Brian ; Buyers, Jane ; Caines, Derek ; Calzolari, Loris ; Carmichael, Catharine ; Cesta, Carlo ; Chikofsky, Melanie ; Clarkson, David ; Cloney, Helen ; Coad, Wendy ; Collins, Paul ; Daley, Cathy ; Dean, Tom ; Dickson, Lee ; Doyle, Alta Louise; Frenkel, Vera; Galbraith, Elinor Rose; Garnet, Carla; Duke, Bill; Dunning, Christopher Lee; Dutrisac, Raymond; Fabo, Andy ; Fast Wurms ; Flack, Robert ; Fortune, Edward ; Girling, Oliver ; Goldstein, Sybil ; Gray, Peter ; Garnet, Eldon ; Gawad, Adly ; General Idea (Collective) ; Guest, John ; Hall, Alexandra ; Harley, Matt ; Harman, Mark ; Harris, Stephen ; Hart, Jamie ; Hassan, Jamelie ; Hylinsky, David ; Holubizky, Ihor ; Koeper, Michael ; Iacobelli, Mauro ; Jocelyn, Tim ; Joffre, Denis ; Johnson, Rae ; Kelley, Hillary ; Klunder, Barbara ; Koeper, Michael ; Kohn, Marty ; Kozzi, Kim ; Lapointe, Norman ; Lee, Susan ; Leeming, Frances ; Leverman, Peter ; Macgregor, John ; Mccallum, Angus Edward ; Mccarthy, Deborah ; Mcgrath, Jerry ; Mckinnon, John ; Merrill, Michael ; Meteor ; Marie, Dyan ; Malouf, Margret ; Mars, Tanya ; Martyn, Carol ; Miller, Bernie ; Monihan, Tom ; Morrison, Doug ; Moore, David ; Moscowitz, Corolyn ; Neighbour, Lisa ; Niblock, Stephen ; Nikolajevich, Annie ; Noestheden, John ; Novaes, Teresa ; Oberst, Paul ; Olanick, Natalie ; Oliver, Jak ; Orlando, Dana ; Ottman, Rod ; Pagani, John ; Peterson, Andy ; Penny, Evan ; Phillips, Paulette ; Pilis, Alexander ; Porter, Dace ; Quasi Modo ; Quigley, Warren ; RAINBOW ROOM, The ; RANDY & BERENICCI ; Radigan, Chris; Rawson, Robin; Roberts, Ralph ; Roche, David ; Roe, Brent ; Rotenberg, Rachel ; Stagg, Sandy ; STEWART, ROBERT (TOXIC)
STRUNTZ, O. (REMO) ; Salloum, Jayce ; Schmid-Esler, Annemarie ; Schwarz, Judith ; Scott, Brian ; Scott, John ; Slonetsky, Leo ; Thibert, Patrick ; Tod, Joanne ; Vent, Erella ; Video, Brian ; Voyce, Julie ; Venables, Paul ; Wagman, Lorne ; Walker, Doug ; Walmsley, Ben ; Wiens, Robert ; West, Shane ; Wilson, Amy ; Wilson, Tony ; White, Carolyn ; Wolff, Debbie ; Wurstlin, Michael ; Youds, Robart ; YOUNG, SUE (TOXIC)
In October-November 1983 ChromaZone presented the Chromaliving exhibition in the vacant Harridges department store in the heart of downtown Toronto. This huge sprawling installation of artist-made furniture, fashion, interior decor and installations by 150 artists was the hit of the fall art season.
boek